A platform for large-scale graphene electronics--CVD growth of single-layer graphene on CVD-grown hexagonal boron nitride - Wang, Min (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.